2003
DOI: 10.1105/tpc.011056
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing Modulation by a LAMMER Kinase Impinges on Developmental and Transcriptome Expression

Abstract: Alternative splicing is a major contributor to genome complexity, playing a significant role in various cellular functions, including signal transduction, immunity, and development. The spliceosomal machinery is responsible for the processing of nuclear RNA. Several splicing factors associated with this complex are phosphorylated by kinases that possess a conserved LAMMER motif. We demonstrate in BY-2 tobacco cells a novel role for the LAMMER motif in the maintenance of proper subnuclear localization. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 63 publications
(85 reference statements)
0
53
0
1
Order By: Relevance
“…tabacum cv Samsun was transformed as previously described (Horsch et al, 1985). N. tabacum cv BY2 cell suspension were transformed as described by Savaldi-Goldstein et al (2003).…”
Section: Plant and Cell Suspension Transformationmentioning
confidence: 99%
“…tabacum cv Samsun was transformed as previously described (Horsch et al, 1985). N. tabacum cv BY2 cell suspension were transformed as described by Savaldi-Goldstein et al (2003).…”
Section: Plant and Cell Suspension Transformationmentioning
confidence: 99%
“…To examine the in vivo effects of PK12, a construct of the tobacco gene was introduced into Arabidopsis (which contains a homologous protein with 73% amino-acid identity) where it was shown to bind, phosphorylate and colocalize with the Arabidopsis splicing factor atSRp34/ SR1 (Savaldi-Goldstein et al, 2003). Lines expressing high levels of the transgene had high PK12 kinase activity and showed altered patterns of AS in three of the four splicing factor genes that were examined (Figure 4a), i.e.…”
Section: As and The Generation Of Plastic Organism-level Phenotypesmentioning
confidence: 99%
“…Members of the LAMMER subfamily occur in a variety of organisms from yeast to human [5][6][7][8][9][10][11], showing a high degree of conservation in those domains that are essential for phosphotransfer and substrate recognition [12]. Furthermore, the ability of several LAMMER kinases to modulate splicing could indicate a common functional role [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, mutations in the LAMMER kinase Doa alter sexual differentiation and activity of the Doa locus is required for development of embryonic tissues [14,32]. It was recently shown that the pk12 LAMMER kinase also modulates development and gene expression in tobacco cells [16].…”
Section: Introductionmentioning
confidence: 99%